Terapi Pengganti Ginjal pada Sepsis Disertai dengan Status Hiperosmolar Hiperglikemia dan Cedera Ginjal Akut - Mutiara, Gunawan; , Indriasari (Jurnal Komplikasi Anestesi, 2020)
Acute kidney injury was a complication recently occurred in critical ill patients in ICU. A 64 years old man came to emergency department with chief complain of lump originated at colli dextra accompanying with difficult of breathing symptom. Patient was diagnosed with septic shock due to deep neck abcess complicated with AKI and uremic encephalopathy, diabetes mellitus type 2 with hyperosmolar hyperglycemia state. Patient was treated to manage dehydration, high blood glucose, and source control of infection, then patients was transferred to ICU with support of mechanical ventilator. The major problem of this patients was decrease of consciousness and difficulties in treating AKI stage because there were increase in serum ureic and creatinine level even though urine production was excessive. Patients condition was improved and could be extubated after performing renal replacement therapy on the sixth day. On patients with sepsis with AKI, renal replacement therapy was one of the modalities considered to support management in critical ill patients in ICU.